Financial Performance Analysis in Measurement of Bank Soundness Level (Study At PT. Bank Sulutgo 2016-2020 Period). - Tirza Mantik; Herman Karamoy; Maryam Mangantar (Research Parks Publishers, 2021)
This study aims to analyze financial performance in measuring bank soundness as measured using the RGEC (Risk Profile, Good Corporate Governance, Earnings, Capital) method at PT. Bank SulutGo period 2016 - 2020. The data analysis method in this study is descriptive analysis with a quantitative approach. The results showed that the Bank's Health Level based on the risk profile factor showed that the bank's NPL was below 2% which was predicated as very healthy, and the LDR was predicated as unhealthy. The Good Corporate Governance factor shows that the bank gets a healthy predicate. The earnings factor shows that the bank's ROA is more than 1.5% which is predicated as very healthy and the bank's NIM is more than 3% which is predicated as very healthy.